Gyrfalcon, Falco rusticolus L. - Snow, Carol.; United States. Bureau of Land Management. Denver Service Center. (Denver : Bureau of Land Management, U.S. Dept. of the Interior, Denver Service Center, 1974)
Cover title. Bibliography: p. 13-14. Mode of access: Internet.